A New Design of Compact 4×4 Butler Matrix for ISM Applications. (25th February 2009) - Traii, Mbarek; Nedil, Mourad; Gharsallah, Ali; Denidni, Tayeb A.
Abstract : A novel design of a compact4 × 4 Butler matrix is presented. All the design is based on the use of a Lange coupler with certain geometrical characteristics. This matrix occupies only 20% of the size of the conventional Butler matrix at the same frequency (80% of compactness). To examine the performance of the proposed matrix, the Lange coupler and the Butler matrix were simulated using Momentum (ADS) and IE3D softwares. Simulation results of magnitude and phase show a good performance. Furthermore, a four-antenna array was also designed at 2.45 GHz and then connected to the matrix to form a beamforming antenna system. As a result, four orthogonal beams at− 45 ∘, − 15 ∘, 15 ∘, and45 ∘ are produced. This matrix is suitable for wireless application at ISM band of 2.45 GHz.